(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Wild edible mushrooms are consumed in the center regions of Côte d’Ivoire. In this study, the proximate composition, mineral element profile and amino acid profile of two selected wild edible mushrooms from three regions from center of Côte d’Ivoire including Lentinus squarrosulus and Auricularia politrich investigated. The mushrooms were harvested fresh, dried in an oven at 45°C for 48 hours, ground and analyzed according to standard procedures. showed high level of proteins (24.07±0.30–26.20±0.72%), crude fibre (12.30±0.07–20.13±0.07%), carbohydrate (52.36±1.84–64.64±0.68%), ash (9.58±0.18–16.02 ±0.10%) and fat (0.92±0.02–5.40±0.24%) in all species in the three regions. Mineral analysis of all species indicated the mushrooms were specifically rich in potassium, phosphorus, calcium and magnesium. Potassium was found to be the most abundant mineral present in all specie ranging from 1240.02±0.20 to 3414.11±0.94 mg/100g. Cadmuim and lead contents of the two species were generally very low. There were 17 amino acids, and these mushrooms were rich in essential amino acids. The ratios of essential amino acids to total amino acids were 0.40 to 0.45. The high scores of essential amino acids present in these mushrooms implied that they have a high biological protein value. These mushrooms could be considered a potential health food and may be of use to the food industry as a source of ingredients with high nutritional value.